(untitled) (XXI Century. Spanish Literature and Culture, 2015)
It would be with no disrespect to the newest narrative approaches to settle the realistic tradition as the place of origin of the Spanish novel today, and the attempt to reflect as accurately as possible life as it is and things as they have been as the direction of its several pathways. It is not but with unyieldingly reliance and thoroughness that the Valencian novelist Rafael Chirbes (1942) follows this direction. He has done it in fulfilling his novels, from Mimoun (1988) to the recent En la orilla (2013), throughout a quarter century of novelistic journey, counting two masterworks –La larga marcha (1996) and La caída de Madrid (2000), which Max Aub’s Campos sedimented Galdosian heritage cannot go unrecognised by a savvy reader, far less by a literary historian.